Beliefs and Utility: Experimental Evidence on Preferences for Information - Armin Falk; Florian Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2016)
Beliefs are a central determinant of behavior. Recent models assume that beliefs about or the anticipation of future consumption have direct utilityconsequences. This gives rise to informational preferences, i.e., preferences over the timing and structure of information. Using a novel and purposefully simple set-up, we experimentally analyze preferences for information along four dimensions. We find evidence that the majority of subjects prefers receiving information sooner. This preference, however, is not uniform but depends on context. When the environment allows subjects to not focus attention on (negative) consumption events, later information becomes more attractive. We also identify an aversion towards piecemeal information. Variations in prior distributions do not seem to affect information preferences.
Keywords: C91; D03; D12; D83; 330; beliefs; anticipatory utility; news utility; information preferences; attention; reference-dependent preferences; experiments